Analysis of the extent of limbic system changes in multiple sclerosis using FreeSurfer and voxel-based morphometry approaches. - Amanda Frisosky Abuaf; Samuel R Bunting; Sara Klein; Timothy Carroll; Jake Carpenter-Thompson; Adil Javed; Veronica Cipriani (PLoS ONE, 2022)
Background and purpose The limbic brain is involved in diverse cognitive, emotional, and autonomic functions. Injury of the various parts of the limbic system have been correlated with clinical deficits in MS. The purpose of this study was to comprehensively examine different regions of the subcortical limbic system to assess the extent of damage within this entire system as it may be pertinent in correlating with specific aspects of cognitive and behavioral dysfunction in MS by using a fully automated, unbiased segmentation approach. Methods Sixty-seven subjects were included in this study, including 52 with multiple sclerosis (MS) and 15 healthy controls. Only patients with stable MS disease, without any relapses, MRI activity, or disability progression were included. Subcortical limbic system segmentation was performed using the FreeSurfer pipeline ScLimbic, which provides volumes for fornix, mammillary bodies, hypothalamus, septal nuclei, nucleus accumbens, and basal forebrain. Hippocampus and anterior thalamic nuclei were added as additional components of the limbic circuitry, also segmented through FreeSurfer. Whole limbic region mask was generated by combining these structures and used for Voxel-based morphometry (VBM) analysis. Results The mean [95% confidence interval] of the total limbic system volume was lower (0.22% [0.21-0.23]) in MS compared to healthy controls (0.27%, [0.25-0.29], p < .001). Pairwise comparisons of individual limbic regions between MS and controls was significant in the nucleus accumbens (0.046%, [0.043-0.050] vs. 0.059%, [0.051-0.066], p = .005), hypothalamus (0.062%, [0.059-0.065] vs. 0.074%, [0.068-0.081], p = .001), basal forebrain (0.038%, [0.036-0.040] vs. 0.047%, [0.042-0.051], p = .001), hippocampus (0.47%, [0.45-0.49] vs. 0.53%, [0.49-0.57], p = .004), and anterior thalamus (0.077%, [0.072-0.082] vs. 0.093%, [0.084-0.10], p = .001) after Bonferroni correction. Volume of several limbic regions was significantly correlated with T2 lesion burden and brain parenchymal fraction (BPF). Multiple regression model showed minimal influence of BPF on limbic brain volume and no influence of other demographic and disease state variables. VBM analysis showed cluster differences in the fornix and anterior thalamic nuclei at threshold p < 0.05 after adjusting for covariates but the results were insignificant after family-wise error corrections. Conclusions The results show evidence that brain volume loss is fairly extensive in the limbic brain. Given the significance of the limbic system in many disease states including MS, such volumetric analyses can be expanded to studying cognitive and emotional disturbances in larger clinical trials. FreeSurfer ScLimbic pipeline provided an efficient and reliable methodology for examining many of the subcortical structures related to the limbic brain.